Learning at School and Work : Boundary crossing, strangeness and legitimacy in apprentices' everyday life - Tanggaard, Lene [Verfasser] (My University, 2008)
"This article argues for a situated approach to understanding learning in the fields of school and the workplace in vocational education (Lave & Wenger 1991; Hodkinson 2005; Tanggaard 2006). The purpose of the article is to show that boundary crossing and the relation between strangeness and legitimacy of participation is a central dynamic in situated learning across different practices such as school and the workplace (Bowker & Star 1999). The article is mainly theoretical, but it draws on examples from a recent qualitative field study of learning among apprentices in the Danish vocational education (Tanggaard 2005)." (Autorenreferat, BIBB-Doku)
Keywords: L 2.1 Lernformen; I 2.2.1 Westeuropa; Berufsbildung; Lernort Betrieb; Lernort Schule; Situiertes Lernen; Handlungsorientiertes Lernen; Dänemark